2015
DOI: 10.1097/mbc.0000000000000257
|View full text |Cite
|
Sign up to set email alerts
|

Changes in bleeding patterns in von Willebrand disease after institution of long-term replacement therapy

Abstract: Clinically, the leading symptom in von Willebrand disease (VWD) is bleeding, chiefly of mucosal type, for example, epistaxis, gingival, or gastrointestinal bleeding, and menorrhagia. In severe forms of VWD with secondary deficiency of factor VIII, spontaneous joint bleeding, resembling that observed in severe haemophilia A, may also be observed. The bleeding patterns of VWD can affect quality of life, and may be life-threatening. The von Willebrand Disease Prophylaxis Network is an international study group fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(69 citation statements)
references
References 7 publications
0
59
1
Order By: Relevance
“…The von Willebrand Disease Prophylaxis Network (VWD PN) is an international study group formed with the goal of evaluating prophylactic regimens for people with clinically severe VWD. Retrospective and prospective studies from the VWD PN showed that prophylactic treatment of severe forms of VWD is efficacious and a significant overall reduction in haemorrhages occurred after initiation of prophylaxis …”
Section: Introductionmentioning
confidence: 99%
“…The von Willebrand Disease Prophylaxis Network (VWD PN) is an international study group formed with the goal of evaluating prophylactic regimens for people with clinically severe VWD. Retrospective and prospective studies from the VWD PN showed that prophylactic treatment of severe forms of VWD is efficacious and a significant overall reduction in haemorrhages occurred after initiation of prophylaxis …”
Section: Introductionmentioning
confidence: 99%
“…The strategy is similar to hemophilia treatment, where factor concentrates are regularly administered to reduce joint bleeding and its associated long-term morbidity 42,43. Symptomatology in VWD is more variable than hemophilia; joint bleeding is less common and mucosal surface bleeding can be the predominant bleeding pattern 44. Prophylaxis with VWF concentrates significantly reduces mucosal and joint bleeding rates 4446.…”
Section: Treatment Of Vwdmentioning
confidence: 99%
“…Symptomatology in VWD is more variable than hemophilia; joint bleeding is less common and mucosal surface bleeding can be the predominant bleeding pattern 44. Prophylaxis with VWF concentrates significantly reduces mucosal and joint bleeding rates 4446. A recombinant VWF concentrate has also been developed that is effective at stabilizing FVIII47 and controlling bleeding events 48…”
Section: Treatment Of Vwdmentioning
confidence: 99%
“…What is the optimal dosing regimen? Further research is needed and a prospective trial is ongoing in the VWD PN [Holm et al 2015].…”
Section: Should I Use Vwf Concentrate Prophylaxis For Severe Vwd Patimentioning
confidence: 99%
“…A recent update of this study reported continued success with a total of 105 patients. A total of 10 of these patients are enrolled in a prospective study to help ascertain the most appropriate dosing regimen using a dose-escalation strategy [Holm et al 2015].…”
Section: Should I Use Vwf Concentrate Prophylaxis For Severe Vwd Patimentioning
confidence: 99%